Mechanical Alterations during 800-m Self-Paced Track Running - Girard, Olivier; Millet, Gregoire P.; Micallef, Jean-Paul (International Journal of Sports Medicine, 2017)
We assessed the time course of running mechanical alterations during an 800-m. On a 200-m indoor track, 18 physical education students performed an 800-m self-paced run. Once per lap, ground reaction forces were measured by a 5-m-long force platform system, and used to determine running kinetics/kinematics and spring-mass characteristics. Compared with 100 m (19.4±1.8 km.h−1) running velocity progressively decreased at 300, 500 m but levelled-off at 700 m marks (−5.7±4.6, −10.4±8.3, and −9.1±13.5%, respectively; P<0.001). Stride length (−8.5±2.3%, P<0.01) and frequency (−1.0±1.5%, P=0.05) along with peak braking (−7.5±4.4%, P<0.05) and push-off forces (−5.1±7.2%, P<0.05) decreased from 100 m to 700 m. Peak vertical forces (−3.0±2.7%; P>0.05) and leg compression (+2.8±3.9%; P>0.05) remained unchanged, whereas centre of mass vertical displacement (+24.0±7.0%; P<0.001) increased during the run. Vertical stiffness decreased (−18.1±4.4%; P<0.001), whereas leg stiffness was unchanged (−3.2±4.6%; P>0.05). During an 800 m by physical education students, highest running velocity was achieved early during the run, with a progressive decrease in the second half of the trial. While vertical ground force characteristics remained unchanged, non-specialist runners produced lower peak braking and push-off forces, in turn leading to shorter stride length. Spring-mass model characteristics changed toward lower vertical stiffness values, whereas leg stiffness did not change.
Keywords: leg spring behaviour; stride parameters; stiffness; pacing strategy; middle distance running